Hurricane and Tropical Storm Impacts on Prescribed Fire and Wildfire Management Practices - David R. Godwin; Breanne Ward; Jennifer E. Fawcett; Gary C. Wood; Raelene M. Crandall (EDIS)
Hurricanes and tropical storms can significantly alter forested and non-forested areas, creating unique hazards and considerations for wildland firefighters and prescribed burners. Prior to responding to wildfires and planning prescribed fires, fire managers should anticipate how these changes will affect fire behavior, smoke, hazards, and access to the fire.